On a collection of Cirripedia thoracia from Madagascar and adjacent waters - Ren, X. (Bull. Mus. Natn. Hist. Nat., Paris, 1989)
Thoracic cirripeds collected in the Madagascar waters by Alain Crosnier include 28 species belonging to three suborders and nine families. Six species are described as new and six others are recorded for first time from this part of the Indian Ocean.